2022
DOI: 10.3390/ma15062050
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Environmental Impact of Waste Mineral Wool and Mineral in Wool-Based Geopolymer

Abstract: Waste generated in fine wool production is homogeneous and without contamination, which increases its chances of reuse. Waste mineral wool from demolition sites belongs to the specific group of waste. However, the storage and collection require implementing restrictive conditions, such as improper storage of mineral wool, which is highly hazardous for the environment. The study focuses on the leachability of selected pollutants (pH, Cl−, SO42−) and heavy metals (Ba, Co, Cr, Cu, Ni, Pb, Zn) from the waste miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although immobilization in the hardened binders (SCB1 and SCB2) is not total for some metals (e.g., Cr), the concentrations are below the highest permissible values according to the Urban Waste Water Treatment Directive [ 80 , 81 ]. Due to the differences observed between SCM2 and the binders, it can be concluded that the heavy metals were fixed during hardening.…”
Section: Resultsmentioning
confidence: 99%
“…Although immobilization in the hardened binders (SCB1 and SCB2) is not total for some metals (e.g., Cr), the concentrations are below the highest permissible values according to the Urban Waste Water Treatment Directive [ 80 , 81 ]. Due to the differences observed between SCM2 and the binders, it can be concluded that the heavy metals were fixed during hardening.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that the sourcing and reuse of reused materials is a simple way to generate less waste and a dominant trend in deepening the ecological aspect of architecture and construction. Reusing non-obvious materials such as glass [31], concrete pavement [32], mineral wool [33,34], and rubble [35] is reflected in the scientific research and literature of the twenty-first century.…”
Section: Reused Materials-their Features and Rating Of Usefulnessmentioning
confidence: 99%
“…Buildings 2024, 14, x FOR PEER REVIEW 6 of 20 manual labour injury cial protection shredding, stacking, cutting Reusing non-obvious materials such as glass [31], concrete pavement [32], mineral wool [33,34], and rubble [35] is reflected in the scientific research and literature of the twenty-first century.…”
Section: Reused Materials-their Features and Rating Of Usefulnessmentioning
confidence: 99%
“…The mechanical processing of this waste is also a challenge. Mineral fibers, despite their low density, are very abrasive, which causes abrasion to shredding equipment [5]. Moreover, the large volume relative to the low mass makes it economically unjustifiable to transport this waste over long distances.…”
Section: Introductionmentioning
confidence: 99%